Gallium Selective PVC Membrane Electrodes Based on Crown Ethers - Abdulla, N. I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
+ Gallium selective e lectrodes based on 12-crown-4 (12C4) and benzo-15-crown-5 (B15C5) and plasticizers dioctyl phenyl phosphonate (DOPP), dibutyl phosphate (DBP), dibutyl phthalate (DBPH) in PVC matrix membranes are constructed. Specific properties of the electrodes are studied including calibration curve, slope detection limit, concentration range, response time and life tiMe as well as the effect of pH on electrode response. Interference for Li1 , Mg2+, Zn2+, Al 3 +, Cr3+ on electrode respons.e have been also investigated. The polymetic liquid membrane electrode based on 12C4 using DBPH plasticizer exhibits the best over all performances as a gallium selective electrod e over a wide concentration range (l.O x l0-5 - 3.3x10-2 M) with Nemestian slope (20mV/decade). It has a relatively fast response time excellent detection limit (7x 1o-6M) and good durability (about 2 m onths). The electrode revealed a good + selectivity for Ga3 over a variety of other metal ions and could be used in a pH range of 3.0-5.0. It was used as an indicator electrode in potentiometric titration of gallium ions.